Agro-Morphological Characterization and Intra-Varietal Diversity of Akabarechilli (Capsicum spp.) Landraces of Nepal - Karkee, A; Mainali, RP; Basnet, S; Ghimire, KH; Joshi, BK; Thapa, P; Shrestha, DS; Joshi, P; Pokhrel, P; Mishra, KK (SAARC Journal of Agriculture, 2022)
Capsicum (Solanaceae), comprising of sweet and hot chilli pepper, is a globally known spice crop. This genus is well known for its huge genetic diversity at intra- and inter-species level. Diversity among Akabarechilli landraces, a unique Capsicum from Nepal, has not been studied so far. The present study characterized thirty accessions of Akabarechilli using 26 qualitative and 21 quantitative agro-morphological markers at the experimental plots of National Genebank, Khumaltar, Nepal during the summer season of 2018/019. Using principal component analysis, the first- principal components with eigen-values more than 1 contributed 25% of the variability among accessions for quantitative traits, whereas the first principal components with eigen-values more than 1 contributed 22.2% of the variability among accessions for qualitative traits. These findings suggested a wide range of morphological variations among the tested accessions. Based on qualitative and quantitative traits, 30 accessions were grouped into 6 distinct clusters by Euclidian distance and average method. Accessions CO-11048 and CO-11050 under cluster-III were round shape fruit type and accessions CO-11044, CO- 11046 andCO-11047 under cluster-I were high fruiting with longer fruitbearing period and could be utilized for breeding purpose as these are the traits preferred by consumers or processors in Nepalese market. SAARC J. Agric., 19(2): 37-55 (2021)